Callus cell culture of Pothomorphe umbellata (L.) under stress condition leads to high content of peroxidase enzyme - Khalil, Najeh Maissar; Mello, Miriam Alves Morais; França, Suzelei de Castro; de Oliveira, Luiz Antonio Andrade; Oliveira, Olga Maria Mascarenhas de Faria (Eclética Química, 2006)
Pothomorphe umbellata (L.) known on Brazil as Caapeba has a number of popular medicinal use, and it has been studied in relation to its pharmacological activity. Peroxidase specific activity (units/mg protein) was evaluated in callus cell culture samples of the P.umbellata, grown in two different MS medium (media 1 and media 2), submitted to 16 hours photoperiod or kept in darkness. Cell growth rate curve showed that the best growth indices were observed when media 2 submitted to the photoperi- od regime was used, followed by the same media kept in darkness (stress condition). The results obtained also showed that the cell culture grown under stress conditions (darkness) lead to high content of peroxi- dase enzyme (an increase of 700% was observed). Kinetic constant values of 3.3 mmol.L-1 and 2,8 sec-1 were obtained for k M and v max ,, respectively, using guaiacol as enzyme substrate.